The relation between facial prognathism and cervical posture in skeletal class I Iraqi adult sample - Attar, Hayder J; Jinan Aliwee; Hameed, Ali M (Journal of Baghdad College of Dentistry, 2013)
Background: Biologic mechanisms of the form-function interaction are one of important component of orthodontic diagnosis. The purpose of this study is to search for the statistical associations between natural postural and craniofacial morphologic variables of the head. Materials and methods: The sample comprised natural head posture (NHP) cephalograms of 90 subjects, aged 18 to 25 years. Interpretation of the facial structure was made by using both intracranial and the extra-cranial reference lines in AutoCAD computer program. Results The measures of anteroposterior maxillary position, SNA showed a low negative correlations with the anterior cranial base angulation to true vertical (SN.Ver) and with the cranio-cervical position of the head (SN.OPT),(SN.CVT) The measures of anteroposterior mandibular position, SNB and SNPog, both showed moderate correlations with the anterior cranial base angulation to true vertical (SN.Ver) and with the cranio-cervical position of the head (SN.OPT),(SN.CVT) . Conclusion Regarding the correlations between the variables indicating the degree of facial prognathism in the NHP, and the postural variables of the cervical column, it can be argued that in subjects with forward cervical inclination, a relative decrease in facial prognathism is expected.